Audibility of changes in spectral structure of saw-tooth stimuli - H. HARAJDA; W. MIKIEL (Archives of Acoustics)
This paper presents the experiments which provided an answer to the question: what structural changes in the saw-tooth stimuli are likely to affect changes in the colour perception? The sound material of the experiments consisted of signals with structural features which can be found in the signals of natural string instruments. The signals were assumed to be characteristic of the following constant quantities: – harmonic structure composed of successive component tones, – triple time structure: attack-steady state-decay, – gradually decreasing tendency in the level of the spectrum envelope. In the experiments the ATARI computer system was utilized. The groups of observers consisted of 5 subjects well-educated in music and acoustics who went through a special pre-test training. The research findings on the dependence of changes in auditory sensation on the changes in the structure of the saw-tooth stimuli being compared indicate that this relationship assumed a simple form when the variables were either the number of component tones or the decreasing tendency in the level of spectrum envelope.